Kedudukan dan Fungsi Badan Nasional Penanggulangan Terorisme (BNPT) Dalam Pemberantasan Terorisme di Indonesia - Nur Paikah (Al-Adalah: Jurnal Hukum dan Politik Islam, 2019)
This study aims to find out and analyze the position and function of the National Counter Terrorism Agency (Badan Nasional Penanggulangan Terorisme/BNPT). This type of research is normative legal research. The approach used is the legislative approach, conceptual approach and case approach.The results of the study indicate that the BNPT is a non-ministerial state institution under the President and is responsible to the President. In carrying out its duties and functions, BNPT is coordinated with the Coordinating Minister for Politics, Law and Security. The task and function carried out by BNPT is to counter terrorism in Indonesia by using the soft power main approach (prevention). Through a soft power approach BNPT implements two programs, namely deradicalization and counter radicalization. Both of these programs are based on BNPT's view that reducing radicalism does not always have to use a repressive approach as done by the police in general. Law enforcement must be balanced with preventive measures (prevention) by using a pattern of humanitarian approaches so as not to create a sense of revenge and give birth to a new form of violence.